2021
DOI: 10.1111/ijfs.15438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of superchilling on quality of crayfish (Procambarus clarkii): water migration, biogenic amines accumulation, and nucleotides catabolism

Abstract: Effects of refrigerated (3.5 AE 0.5 °C), iced (0 AE 0.5 °C) and superchilled (−3.0 AE 1.0 °C) storage on quality of crayfish (Procambarus clarkii) were evaluated by monitoring the water migration, microbial contamination, biogenic amines accumulation, and nucleotides catabolism during 21 days. The results indicated that superchilling was effective in accelerating the rate of water migration and reducing total volatile basic nitrogen, trimethylamine, total viable bacteria, Enterobacteriaceae and psychrotrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…1 (A). The initial pH value of CMSS (6.16) was lower than that of fresh crayfish (6.44) reported by Qin et al (2022) . This disparity may be attributed to the acceleration of glycolysis in CMSS following homogenization treatment accompanied by the high temperature, leading to the tremendous accumulation of acidic substances or hydrogen ions.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…1 (A). The initial pH value of CMSS (6.16) was lower than that of fresh crayfish (6.44) reported by Qin et al (2022) . This disparity may be attributed to the acceleration of glycolysis in CMSS following homogenization treatment accompanied by the high temperature, leading to the tremendous accumulation of acidic substances or hydrogen ions.…”
Section: Resultscontrasting
confidence: 61%
“…The ascertainment of TVB-N and TMA contents was carried out by the method of Qin et al (2022) . The homogenate, a mixture of minced muscles(10 g )and 20 g/L trichloroacetic acid (50 mL), was made at a speed of 946 ×g for 1 min by a high-speed disperser (Scientz, Ningbo, China).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the TVB-N level can be used as an important indicator to estimate the freshness of crayfish. It has been recommended that the accepted limit of TVB-N value for aquatic products is 20 mg/100 g, exceeding which indicated inedible products [46] . Accordingly, the crayfish in the control group became unacceptable from the 4th day, individual US group remained acceptable until the 6th day, while PAW or UP groups exceeded the acceptable limit on the 8th day.…”
Section: Resultsmentioning
confidence: 99%
“…The pH values were evaluated according to the method of Qin et al [3]. Briefly, a high-speed disperser (Scientz, Ningbo, China) homogenized 5 g of crayfish muscles with Foods 2023, 12, 2258 3 of 13 50 mL ultrapure water at 8000 r/min for 1 min, and a digital pH meter (Mettler-Toledo, Shanghai, China) was used to determine the pH value.…”
Section: Determination Of Phmentioning
confidence: 99%
“…Meanwhile, the speed of quality deterioration in superchilled products is slower than in conventionally refrigerated, and many researchers in the realm of food preservation are beginning to focus on superchilling technology [2]. Our previous research found that superchilling was effective in reducing trimethylamine (TMA), total volatile basic nitrogen (TVB-N), and biogenic amines of crayfish and also promoting the accumulation of inosine monophosphate (IMP) [3], which act as a flavor enhance [4]. However, compared with refrigeration, the temperature of superchilling was lower and below freezing, which could lead to the formation of ice crystals, bringing negative effects on crayfish muscle tissue.…”
Section: Introductionmentioning
confidence: 99%